SISTEM INFORMASI PENGADUAN MASYARAKAT BERBASIS WEBSITE DI DESA PAGARBATU - Fadhilah, Leni; A. Hamdani; Helyatin Nisyak (CV. Denasya Smart Publisher, 2025)
Advancements in information technology have provided opportunities for village governments to enhance the quality of community services, particularly in managing complaints.. This research discusses a website-based community complaint information system implemented in Pagarbatu Village, Saronggi Sub-district, Sumenep District. The system is designed to replace the conventional method of utilizing a physical complaint box, which is considered less effective in handling community reports. Using the waterfall system development model, this research produced a web-based platform that allows people to submit complaints quickly and easily. The system also provides features for village officials to manage reports in a structured and transparent manner. The results show that the implementation of a web-based complaint information system can improve the efficiency and accountability of public services.